X-ray diffraction studies, thermal, electrical and optical properties of oxovanadium(IV) complexes with quadridentate schiff bases - Sarkar, S; Aydogdu, Y; Dagdelen, F; Bhaumik, BB; Dey, K (Elsevier Science Sa, 2004)
The oxovanadium(IV) complexes with quadridentate schiff bases have been prepared and were characterized by means of X-ray diffraction (XRD), electrical conductivity and optical absorption techniques. X-ray analysis shows that the [VO(L-1)], [VO(L-2)] and [VO(L-3)] complexes have monoclinic structure. The thermal properties of complexes were examined by the method of thermogravimetric analysis. In the thermogravimetric analysis studies 20degreesC min(-1) heating rate was used. Electrical transport properties were studied by do conductivity measurements. The electrical activation energies of the complexes which were in the range of 0.48-1.18 eV were calculated from Arrhenius plots. Optical absorption studies in the wavelength range of 190-1100 nm at room temperature showed that the optical band gap E-g of [VO(L-1)], [VO(L-2)] and [VO(L-3)] complexes were 3.45, 2.65 and 2.80 eV, respectively. The complexes were electrically insulator at room temperature, however, their conductivities increased as the temperature increases from 330 K, indicating their semiconducting behaviour. The semiconducting behaviour of the oxovanadium(IV) complexes with quadridentate schiff bases was determined by their chemical structure, which affords an extended conjugation. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: oxovanadium(IV); quadridentate schiff base; semiconducting behaviour